Does Student’s Education Background Affect Technopreneurship Intention? Insights from College Students in Bandung - Siti Mardiana; Helin Garlinia Yudawisastra; Indra Sasangka (www.amertainstitute.com, 2025)
The study aims at investigating factors affecting college students for entering technopreneurship, and whether their intentions are affected by their education backgrounds. The variables being used in the study are Social Support, Academic Support, Attitude toward Technopreneurship, Technopreneurship Intention, and Education background as moderating variable between Attitude toward Technopreneurship and Technopreneurship Intention. The research method is a quantitative study using PLS-SEM analysis. There are 333 respondents data were collected from students of various universities in Bandung and are valid for being used in the study. The result shows that Social Support and Academic Support are significantly affecting students’ Attitude toward becoming technopreneurs, while the attitude toward technopreneurship significantly affects Technopreneurship Intention. However, the effect of Social Support on Attitude is stronger than Academic Support. The Social Support is the degree of family influence on the students (such as having family background which have strong entrepreneurship values and practices). It is surprising that Academic Support, the degree of influence of the academic institutions toward technopreneurship mindset of the students, have a rather weak effect on the students. This finding is quite a reflection of the technopreneurship education so far in the higher education. Another interesting finding is that the education backgrounds (major) of the students do not significantly moderate the relationship between Attitude toward Technopreneurship and Technopreneurship Intention. That means the intention to become technopreneur is not dominated by students who have an IT-based education. This result is contrary to the assumption that students with IT background are more likely to develop ventures for IT startup company. That is in line with our expectation that a technopreneur can emerge from any major background.